Activation in Ireland: an evaluation of the National Employment Action Plan - McGuinness, Seamus; O'Connell, Philip J.; Kelly, Elish; Walsh, John R. (Dublin, 2011)
"Under the National Employment Action Plan (NEAP), people in receipt of Jobseeker's Benefit (JB) or Jobseeker's Allowance (JA) who reach three months duration on the Live Register are identified by the Department of Social Protection (DSP) and referred to FÁS, the national training and employment authority, for an activation interview. During this interview process, clients may be provided with job search assistance, and some may be referred to employment or training opportunities. The study is based on Live Register administrative data recorded from September 2006 to July 2008, so the evaluation refers to the impact of the NEAP over that time period. ..."